Employing the Stabbing Word Game to Mastery of Arabic Vocabulary for Seventh Grade Students at Islamic Middle School Gresik - Muh Sabilar Rosyad; Robi'atul Adawiyah; Muhammad Hafidz (Naatiq: Journal of Arabic Education, 2024)
This modest research seeks to highlight the excitement of the "Stabbing Word" game in enhancing Arabic vocabulary acquisition among seventh-grade students at Mulana Malik Ibrahim Islamic School, in addition to measuring its impact post implementation. This research follows a quantitative, quasi-experimental approach within a single-group design. Primary and secondary data were collected from various sources using observation, testing, and documentation methods. The data were analyzed using educational statistics, specifically the t-test. The study concludes that there is a positive impact of using the Stabbing Word game on students' vocabulary comprehension, based on pre-test and post-test results. The calculated t-value was 5.97, exceeding the critical t-values of 2.78 (at 1% significance) and 2.06 (at 5% significance). This indicates that the alternative hypothesis is supported. The effect size of employing the Stabbing Word game for Arabic vocabulary acquisition among students was significant at 10172, indicating a very large impact according to Cohen's guidelines. Therefore, the use of this game type is considered effective for enhancing Arabic vocabulary among seventh-grade students